1998
DOI: 10.1002/(sici)1521-4109(199810)10:13<869::aid-elan869>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of Metribuzin

Abstract: Metribuzin [4-amino-6-tert-butyl-3-methylthio-1,2,4-triazin-5(4H)-one] is a widely used weed controlling agent. In aqueous solutions and in 30 % v/v acetonitrile/water solutions it is reduced in two two-electron steps. In both steps protonated forms of azomethine bonds are reduced, in the more positive the 1,6-bond, in the more negative (by about 0.4 V) the 2,3-bond. At pH > 7 the conjugated base is reduced at considerably more negative potentials in a one-electron step. Reduction of both azomethine bonds is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 44 publications
0
20
0
1
Order By: Relevance
“…When the nucleophilic attack on C(5) is hindered or blocked by a bulky substituent, then the addition takes place at C (6) 105 . 1,2,4-Triazinium ions bearing no substituent at both C(5) and C(6) can undergo addition of two methoxide ions, with additions to both N(1)=C (6) and N(4)=C (5) (1) is so favored that the crystalline adduct has been isolated [119]. No crystalline products of these two compounds were isolated in the presence of i-PrOH, sec-BuOH and tert-BuOH and similarly no such adducts were isolated for 1,3-dimethyl-, 6-ethyl-93b and 6-phenyl-2,4-dioxo-1,3,5-triazines 93c 122 .…”
Section: Reactions Of 124-triazinesmentioning
confidence: 99%
“…When the nucleophilic attack on C(5) is hindered or blocked by a bulky substituent, then the addition takes place at C (6) 105 . 1,2,4-Triazinium ions bearing no substituent at both C(5) and C(6) can undergo addition of two methoxide ions, with additions to both N(1)=C (6) and N(4)=C (5) (1) is so favored that the crystalline adduct has been isolated [119]. No crystalline products of these two compounds were isolated in the presence of i-PrOH, sec-BuOH and tert-BuOH and similarly no such adducts were isolated for 1,3-dimethyl-, 6-ethyl-93b and 6-phenyl-2,4-dioxo-1,3,5-triazines 93c 122 .…”
Section: Reactions Of 124-triazinesmentioning
confidence: 99%
“…Reduction in both steps involved the protonated from of azomethine bonds in 1,6-and 2,3-positions. In addition, similar reports [19,21,22] in relation with 2e-reduction of azomethine in triazine ring have been published. These processes involve the uptake of four electrons and one or two H + ions per herbicide molecule yielding non-aromatic products.…”
Section: Cyclic Voltammetry (Cv)mentioning
confidence: 56%
“…Therefore, it can be concluded that the first cathodic peak can follow the above EC mechanism, which is well defined in the reviewed literature. On the other hand, there are a few reports [18,19,[21][22][23] on the electrochemical reduction of 1,3,5-triazine derivatives involving reducible azomethine (C@N-) bonds. For example, Ludvik et al [18] studied electrochemical reduction of metamitron (4-amino-3-methyl-6-phenyl-1,2,4-triazin-5(4H)-one) on static mercury drop electrode (SMDE) in DMF and several other solvents.…”
Section: Cyclic Voltammetry (Cv)mentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction peak of azomethine center shows substantial drop in peak current and cathodic potential shift towards more negative values as the pH increases [47].…”
Section: Voltammetric Studiesmentioning
confidence: 95%